How Achievement Error Patterns of Students With Mild Intellectual Disability Differ From Low IQ and Low Achievement Students Without Diagnoses. (February 2017) - Root, Melissa M.; Marchis, Lavinia; White, Erica; Courville, Troy; Choi, Dowon; Bray, Melissa A.; Pan, Xingyu; Wayte, Jessica
This study investigated the differences in error factor scores on the Kaufman Test of Educational Achievement–Third Edition between individuals with mild intellectual disabilities (Mild IDs), those with low achievement scores but average intelligence, and those with low intelligence but without a Mild ID diagnosis. The two control groups were matched with the Mild ID clinical cases on demographic variables including age, gender, and parental education. Results showed significant differences between the groups on several error factors, particularly between the Mild ID group and the two control groups, and no significant differences between all three groups on six error factors. In addition, the two control groups differed significantly on four error factors. Implications for intervention selection, diagnostic considerations, and future directions for achievement test creation are discussed.